2020
DOI: 10.1016/j.laa.2020.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Signless Laplacian spectral conditions for Hamilton-connected graphs with large minimum degree

Abstract: In this paper, we present a spectral sufficient condition for a graph to be Hamilton-connected in terms of signless Laplacian spectral radius with large minimum degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recently, Chen et al [37], Yu et al [178], and Wei et al [169] independently showed the spectral version of Hamilton-connectedness for graphs with large minimum degree. In 2020, Zhou, Wang and Lu [199] presented the signless Laplacian spectral conditions for Hamilton-connected graphs with large minimum degree.…”
Section: Problem For K-edge-connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chen et al [37], Yu et al [178], and Wei et al [169] independently showed the spectral version of Hamilton-connectedness for graphs with large minimum degree. In 2020, Zhou, Wang and Lu [199] presented the signless Laplacian spectral conditions for Hamilton-connected graphs with large minimum degree.…”
Section: Problem For K-edge-connectivitymentioning
confidence: 99%
“…Moreover, we can verify that δ(G) = δ and q(G) ≥ 2(n − δ) for every G ∈ S (1) n,δ ∪ T (1) n,δ . Theorem 4.30 (Zhou-Wang-Lu [199]). Let δ ≥ 2 and n ≥ n 1 (δ) where n 1 (δ) = δ 4 + 5δ 3 + 2δ 2 + 8δ + 12.…”
Section: Problem For K-edge-connectivitymentioning
confidence: 99%
“…Hung et al [15] studied Hamilton-connectivity of alphabet grid graphs. Zhou et al [16] extended a result of Fiedler and Nikiforov and derived signless Laplacian spectral conditions for Hamilton-connected graphs with large minimum degree. Recently, Shabbir et al [17] studied Hamilton-connectivity in Teoplitz graphs.…”
Section: Introductionmentioning
confidence: 97%
“…Zhou and Wang [19] proved a better condition for a graph to be Hamilton-connected: e(G) ≥ n−t 2 +t 2 +t. Recently, Xu, Zhai and Wang [15] improved the results of [5] and [19].…”
Section: Introductionmentioning
confidence: 99%